Audit Energi Sistem Pencahayaan pada Gedung A - Muhammad Noor Hadi; Alvera Apridalianti Melkias; Aceng Daud (SURYA TEKNIKA, 2024)
The lighting system is an important aspect in supporting life in carrying out daily work to create a comfortable work environment. This research aims to conduct an energy audit of the lighting system in Building A to identify the quality of the lighting system on the 2nd Floor and 3rd Floor of Building A. The method used is in accordance with standards for measuring lighting intensity and lighting power. The results of the lighting system energy audit revealed that 24 areas on the 2nd floor and 27 areas on the 3rd floor did not meet lighting intensity standards, while 2 areas on the 2nd floor and 2 areas on the 3rd floor did not meet lighting power intensity standards according to applicable standards. Based on the research conducted, there are two alternative recommendations for improving the lighting system and can provide energy saving opportunities in three areas on the 2nd floor with a total monthly savings of 84.87 kWh per month and four areas on the 3rd floor with a total savings of 39.75 kWh per month